Usefulness of eicosanoids in exhaled breath condensate (EBC) analysis in children with asthma - Głowacka, Edyta (2012)
Exhaled breath condensate (EBC) analysis is a relatively new method of diagnosing pediatric asthma. The aim of study was to ascertain eicosanoids content in EBC and to evaluate its diagnostic value in children. EBC was collected in 35 atopic asthmatics (12.4 yrs ± 3.1) and in 25 healthy controls (age 11.8 yrs ± 3.2). Validated HPLC-MS2 method was used to measure: PGE2, tetranor-PGEM (PGEM), PGD2, 6ketoPGF1α, 11dehydro-TXB2, LTB4, LTC4, trans-LTC4, LTD4, LTE4, 5HETE, 12HETE, 15HETE, LXA4, EXC4, EXD4, EXE4 in EBC. Levels of 9α,11β-PGF2α, PGF2α and 8iso-PGF2α were determined by GC-NICI-MS. Exhaled nitric oxide levels (FeNO) were measured and bronchial hyperresponsiveness (BHR) was assessed by exercise challenge test in each subject. An analytical approach with the Akaike information criterion was used for multivariate regression modeling of the disease status using the most relevant variables. The following eicosanoids: PGEM (p=0.001), PGD2 (p<0.001), PGF2α (p=0,001), 6keto-PGF1α (p=0.03), LTC4 (p<0.001), trans-LTC4 (p=0.04), 5HETE (p=0.02) and 9α,11βPGF2α (p=0.001) were significantly higher, the level of 11dehydro-TXB2 (p=0.02) was significantly lower in asthmatics compared to controls. The Eicosanoids Asthma Classification Ratio (EACR) was computed as the logistic regression function using four variables: PGEM, PGD2, LTC4 and 5HETE. It was superior to FeNO or BHR as a tool for a
Keywords: children asthma; diagnosis; eicosanoids; exhaled breath condensate